Challenges in enumeration of CTCs in breast cancer using techniques independent of cytokeratin expression. - John Castle; Karen Morris; Susan Pritchard; Cliona C Kirwan (PLoS ONE)
Introduction Given the current postulated plasticity between epithelial and mesenchymal states of migratory cancer cells the detection of non-epithelial CTCs is an important scientific and clinical goal. Methods We used the filtration-based ISET technology to enrich circulating tumour cells (CTCs) in early breast cancer blood samples and identify them using a morphology-based immunocytochemistry (ICC) approach. Results We found greater numbers of putative CTCs by this approach than by the cytokeratin-based CellSearch technology, but a high number of CTC false positives were identified in healthy volunteer samples which were not reduced in successive blood draws. Preliminary work using an oestrogen receptor (ER)-based multiplex ICC method in metastatic breast cancer ISET samples indicated a low number of ER+ CTCs even at this advanced stage. Conclusions This work highlights the challenges in enumerating CTCs without conventional epithelial markers.